Tourism employment and economic growth in Albania: An empirical assessment - Toma, Volfrida (Edelweiss Applied Science and Technology, 2025)
This study examines the impact of tourism employment on Albania’s economic growth from 2014 to 2023, with a focus on the accommodation sub-sector. Using secondary data from INSTAT, UNWTO, and the World Bank, the study applies Pearson correlation and linear regression models via SPSS. GDP per capita is the dependent variable, while tourism and accommodation employment serve as independent variables. A strong, statistically significant positive correlation exists between tourism employment and GDP per capita. The simple regression model shows that each additional 1,000 tourism employees corresponds to an increase of approximately USD 30.43 in GDP per capita. Employment in accommodation services exhibits a higher marginal effect. However, severe multicollinearity between the two employment variables limits the interpretability of individual coefficients in the multiple regression model. Tourism employment plays a vital role in Albania’s economic growth, particularly through the accommodation sub-sector, though overlapping variables must be cautiously interpreted. The findings support employment-oriented tourism policies, improved vocational training, and targeted investments in high-value sub-sectors to enhance sustainable and inclusive economic development.